2012
DOI: 10.26727/njrcm.2012.1.1.35-40
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Pattern among the Adolescent Girls: A Study in the Social Welfare Hostels for Schedule Castes, Nellore City, A.P, India

Abstract: WHO defines Adolescence as the segment of life between the ages of 10-19 years. Adolescence is a transition phase through which a child becomes an adult. It is characterized by rapid growth and development; physiologically, psychologically and socially. 1 85% of them live in developing countries. 2 About one-fifth of India's population is in the adolescent age group of 10-19 years. Adolescents constitute a sizeable proportion of the Indian mothers. In Andhra Pradesh, this segment constitutes approximately 5.03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…8 Susmitha et al in their study observed 0.73% lymphadenopathy. 3 In the present study, significantly higher hair problems were in rural than urban adolescent school girls with an overall 16.4% girls were suffering with hair problems.…”
Section: -7mentioning
confidence: 68%
See 2 more Smart Citations
“…8 Susmitha et al in their study observed 0.73% lymphadenopathy. 3 In the present study, significantly higher hair problems were in rural than urban adolescent school girls with an overall 16.4% girls were suffering with hair problems.…”
Section: -7mentioning
confidence: 68%
“…These results are in accordance with that reported by Susmitha et al (12.36%). 3 Singh et al also reported defective vision in 4.5% girls. 8 This difference may be due to inadequate indoor lighting.…”
Section: -7mentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Basu et al (9) it was seen that only 13.6% girls were without any health problem, but 86.4% had one or more health problems. The present study thus corroborates with the above studies of different workers.…”
Section: Discussionmentioning
confidence: 99%
“…In Andhra Pradesh, a study done by Susmitha KM et al reported that pallor (41%), dysmenorrhoea (43.6%), dental caries were the leading causes of morbidity in adolescents. 6 The difference in the morbidity pattern could be due to regional variation. External injuries are common among males, a study from Delhi reported that about 77.5% of adolescents are at risky behaviors, leading to road-traffic accidents and deaths.…”
Section: Discussionmentioning
confidence: 99%